2015
DOI: 10.1063/1.4913894
|View full text |Cite
|
Sign up to set email alerts
|

A two-dimensional coding design for staggered islands bit-patterned media recording

Abstract: This paper proposes a two dimensional (2D) staggered recorded-bit patterning (SRBP) coding scheme for staggered array bit-patterned media recording channel to alleviate the severe 2D interference, which requires no redundant bits at the expense of increased an additional memories. Specifically, a data sequence is first split into three tracks. Then, each data track is circularly shifted to find the best data pattern based on a look-up table before recording such that the shifted data tracks cause the lowest 2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Results show that the magnetization states (or magnetic field) of the surrounding islands must be taken into account when designing the two-dimensional (2D) modulation code 30 to avoid the bad data patterns to be recorded onto a medium. It can also be concluded that the staggered island arrangement helps improve the error performance of the HDMR system, 31 if compared to the square island arrangement.…”
Section: A Array Vs Staggermentioning
confidence: 99%
“…Results show that the magnetization states (or magnetic field) of the surrounding islands must be taken into account when designing the two-dimensional (2D) modulation code 30 to avoid the bad data patterns to be recorded onto a medium. It can also be concluded that the staggered island arrangement helps improve the error performance of the HDMR system, 31 if compared to the square island arrangement.…”
Section: A Array Vs Staggermentioning
confidence: 99%